Review of the phenotypes and genotypes of Bardet-Biedl syndrome from China - Xin-Yi, Zou; Yang-Li, Dai; Ling-Hui, Zeng (Frontiers in Genetics, 2023)
Objective: To analyze the phenotypes, genotypes, and the relationship of phenotypes and genotypes for Chinese patients with Bardet-Biedl syndrome (BBS). Methods: The Chinese Wanfang and Weipu data, and PubMed were searched up to Dec 2022. Patients with detailed clinical feature data were involved in the analysis. Results: A total of 153 Chinese patients, including 87 males, 53 females, and 12 unknown, were enrolled. Their ages ranged from 1.2 to 44 years old with a mean of 16.70 ± 9.90 years old. Among these patients, 80 (52.29%) were reported by ophthalmologists, and only 24 (15.68%) repoted by pediatricians. Most patients (132/137, 96.35%) had visual problems; 131/153 (85.62%) had polydactyly; 124/132 (93.93%) were overweight or obese; 63/114 (55.26%) had renal abnormalities; kidney dysfunction was found in 33 (21.57%); 83/104 (79.81%) had hypogonadism and/or genital hypoplasia; and 111/136 (81.62%) had mental retardation. In this series, genetic analysis was performed in 90 (58.82%) patients, including 22 BBS7 (24.71%), 20 BBS2 (22.73%), and 10 BBS10 (11.24%) patients. Moreover, 11 fetuses were diagnosed prenatally in the last 4 years except for one patient in 2004 year. It was noted that BBS7 had higher penetrance. BBS2 had higher hearing impairment and lower renal abnormality penetrance. BBS10 also had lower renal abnormality penetrance as well. Conclusion: Misdiagnosis or miss diagnosis of BBS may be common in China. In patients with polydactyly, visual impairment, obesity, renal abnormalities, hypogonadism, and mental retardation, or in fetuses with polydactyly and/or renal abnormalities, BBS should be considered in the differential diagnosis. Other deformities should be evaluated carefully and genetic analysis should be performed as early as possible.